Highly Efficient Regioselective Decanoylation of Hyperoside Using Nanobiocatalyst of Fe3O4@PDA-Thermomyces lanuginosus Lipase: Insights of Kinetics and Stability Evaluation - Bi, Yanhong; Wang, Zhaoyu; Tian, Yaoqi; Fan, Haoran; Huang, Shuo; Lu, Yihui; Jin, Zhengyu (Frontiers in Bioengineering and Biotechnology, 2020)
The immobilization of Thermomyces lanuginosus lipase on polydopamine-functionalized Fe3O4 magnetic nanoparticles (Fe3O4@PDA-TLL) as a nanobiocatalyst was successfully performed for the first time, and the Fe3O4@PDA-TLL was used for regioselective acylation of natural hyperoside with vinyl decanoate. The effects of several crucial factors, such as the reaction solvent, substrate molar ratio, temperature, and immobilized enzyme dosage, were investigated. Under optimum conditions, the reaction rate, 6''-regioselectivity, and maximum substrate conversion were as high as 12.6 mM/h, 100%, and 100%, respectively. An operational stability study demonstrated that the immobilized enzyme could maintain 90.1% of its initial maximum conversion even after reusing it five times. In addition, further investigations on the kinetic parameters, like Vmax, Km, Vmax/Km, and Ea, also revealed that the biocompatible Fe3O4@PDA could act as an alternative carrier for the immobilization of different enzymes.